Health‐care transition after Kawasaki disease in patients with coronary artery lesion. Issue 3 (25th March 2018) - Kamiyama, Hiroshi; Ayusawa, Mamoru; Ogawa, Shunichi; Saji, Tsutomu; Hamaoka, Kenji
Abstract: Background: Discussion of health‐care transition (HCT) for adults with a childhood history of coronary artery lesions (CAL) after Kawasaki disease (KD) is important. A nationwide questionnaire survey was performed with support by the Japanese Society of Kawasaki Disease. The purpose of this study was to clarify the reality of HCT and loss to follow‐up in patients with CAL after KD. Methods: The survey was emailed to 48 members of the Japanese Society of Kawasaki Disease from May to July 2014. Results: Forty surveys were collected, giving a response rate of 83.3%. Sixty‐five percent of the respondents belonged to a university hospital. Approximately 90% of the respondents dealt with patients who needed HCT, and 55% had patients who completed HCT. Approximately 70% of the respondents considered that pediatricians should continue sharing HCT information with cardiologists. More than 95% of the respondents had a favorable or average impression of HCT care provided by cardiologists. The percentage of respondents who had loss to follow up for HCT was >40%. Conclusion: Adult cardiologists began managing patients with CAL after KD in more than half of the institutes in this study. Pediatricians should construct a support program for better management of these patients and for cooperation with cardiologists to prevent loss to follow up.